PROBLEMATIKA DAKWAH DI TENGAH PROPAGANDA AGAMA DI MEDIA SOSIAL (PERSPEKTIF KOMUNIKASI POLITIK ISLAM) - Firdaus Muhammad; Khaerunnisa Khaerunnisa (Fakultas Dakwah dan Komunikasi, 2020)
Religious propaganda through social media is quite massive and varied as part of the problems of contemporary propaganda. Hoax pack is quite dominating. Religion becomes a propaganda tool and political commodity and other interest agenda. In this context the religious process is interpreted to be a commodity of propaganda filled with hatred, misguided interpretation of a lie so that the face of religion becomes opaque, congested with slander and fighting which leads to conflict. Indeed religion becomes sacred and spreads peace. But on hoax-laden social media, the face of religion is covered in unusual information from the values of peace and truth of the religion itself. Especially if it touches on practical political issues, religion sometimes becomes a mere propaganda tool. The face of religion on social media looks so bad that there must be an ongoing process of education.